Purification of antioxidants from olive oil mill waste by aqueous two-phase extraction systems - Ayaz, Merve. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2021., 2021)
By-products generated during olive oil production threat to the environment due to high phenolic content. Various treatment alternatives investigated so far are not effective to eliminate toxic phenolic compounds (PCs) from this waste. In this study, instead of olive mill wastewater (OMWW) treatment the recovery of PCs was aimed considering their antioxidant properties. Hence, the separation of antioxidants from the waste does not only reduce its toxicity, but also can supply raw material for the various industries. The OMWW from two-phase centrifugal olive oil extraction process was first concentrated by mechanical vapor recompression (MVR) evaporator. Then two different aqueous two-phase extraction (ATPE) systems based on ethanol/salt having acidic and basic nature were applied to concentrated waste (OMWC). The effects of volume ratio (Vr) and tie line length (TLL) that were the variables of ATPE were investigated for the partitioning of organic components of OMWC. While phase forming ability of basic salt, K2HPO4 in ATPE was higher, the performance of ATPE system with acidic salt, (NH4)2SO4 was found better for the separation of carbohydrates. Increasing TLL and VR enhanced the extraction of total PCs. The ATPE system with 29.18% EtOH and 18.00% salt provided 93.59% total PCs recovery while the elimination rates of carbohydrates and proteins were obtained as 76.05% and 53.47%, respectively. Special attention has been devoted to hydroxtyrosol (HTyr) among PCs since it is abundant in OMWW. High HTyr (35.43 mg/g) and high antioxidant activity (32.29 mg AAE/g) determined by DPPH antioxidant assay were well correlated in ethanol extracts.
Keywords: Olive oil mills.; Olive oil industry -- Waste disposal.; Olive oil industry -- Waste minimization.; Olive oil industry -- Environmental aspects.